Answer:
The value of k ⇨
Step-by-step explanation:
⟺ Substitute a = 4 and b = -7 in the equation.
From
![y=ax^2+3x+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/1w4ir1n8j9g4ght5uyie7btwq0hpdbjcwb.png)
Our new equation is
![y=4x^2+3x-7](https://img.qammunity.org/2021/formulas/mathematics/high-school/vemm7iadnikllf0xlamf581is0wv9lugyl.png)
⟺ Use the formula of finding k value.
![k=(4ac-b^2)/(4a)\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/ze6ipf6s9itbom8hamo2k1fvtvo2g9e94r.png)
⟺ Substitute a = 4 b = 3 and c = -7 in the formula. (Arranged Expression)
![k=(4(4)(-7)-(3)^2)/(4(4))\\k=(-112-9)/(16)\\k=-(121)/(16)\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/65meluqi4rzkd6kayn97ubcb6sibq2um6k.png)
If you are curious where k-value/term comes form, it comes from this equation.
![y=a(x-h)^2+k](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8p1sxsgegitwlyo0h3hri0gwrs8yt9xyxk.png)